2017
DOI: 10.1016/j.amepre.2017.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Screening and Incidence by Age: Unmet Needs Near and After the Stopping Age for Screening

Abstract: Introduction Leading professional organizations recommend cervical cancer screening for average-risk women aged 21–65 years. For average-risk women aged >65 years, routine screening may be discontinued if “adequate” screening with negative results is documented. Screening is recommended after age 65 years for women who do not meet adequate prior screening criteria or are at special risk. Methods Authors examined the most recent cervical cancer incidence data from two federal cancer surveillance programs for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 13 publications
2
53
0
Order By: Relevance
“…Several studies have found lower participation in screening programs among older groups of women than in younger patients . Some authors have reported that most 65‐year‐old patients do not fulfill all criteria for leaving cervical screening .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found lower participation in screening programs among older groups of women than in younger patients . Some authors have reported that most 65‐year‐old patients do not fulfill all criteria for leaving cervical screening .…”
Section: Discussionmentioning
confidence: 99%
“…According to 2015 data from the NHIS, 86% of NH black women and 85% of NH white women were up to date on cervical cancer screening (Table ). A recent study, however, found substantially lower screening prevalence among older women; for example, 22% to 24% of NH black women aged 61 to 70 years had not had a Papanicolaou test within 5 years, compared with 7% among those aged 41 to 45 years …”
Section: Selected Findingsmentioning
confidence: 92%
“…An estimated 2,250 new cases of invasive cervical cancer and 770 deaths are expected to occur among black women in 2019. The incidence rate of cervical cancer is 30% higher in NH black women than in NH white women (Table ) with the largest disparity among older women . The black‐white disparity is even greater when incidence rates are adjusted for hysterectomy prevalence, which is higher in black women .…”
Section: Selected Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer registries have been used to provide compelling data documenting variations in cancer incidence and cancer mortality within and among different populations . Combined data from the NPCR and SEER registries have provided sufficient numbers of incident cases to examine rare cancers, specific histologic types, cancers at specific ages, and regional variations . In addition to contributing critical knowledge regarding patterns in cancer occurrence and a resource for cancer researchers, cancer surveillance data provide essential data with which to guide cancer prevention and control activities at the national, state, and local levels.…”
Section: Discussionmentioning
confidence: 99%